2012
DOI: 10.1080/10590501.2012.653887
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxicity and Environmental Transformation of Polycyclic Aromatic Hydrocarbons (PAHs)—Light-Induced Reactive Oxygen Species, Lipid Peroxidation, and DNA Damage

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a class of mutagenic and tumorigenic environmental contaminants. Although the mechanisms by which PAHs induce cancer in experimental animals have been extensively studied and the metabolic activation pathways have been determined, the environmental fate of PAHs and the phototoxicity exerted by PAHs, as well as their photoreaction products formed in the environment, have received much less attention. In this review, the formation of oxygenated PAHs, PAH quinones, nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(102 citation statements)
references
References 169 publications
(263 reference statements)
1
100
0
1
Order By: Relevance
“…Many studies have been revealed that the capacity of insect detoxification enzymes to be induced by xenobiotic and the relationship between elevated detoxifying enzyme levels and tolerance to chemical insecticides. 53 Our work demonstrates that Cadmium chloride and Lead nitrate exposure against larval tolerance and antioxidant enzymes. Our results confirm that both Cd and Pb heavy metals induced toxicity and significantly increased antioxidant enzymes.…”
mentioning
confidence: 99%
“…Many studies have been revealed that the capacity of insect detoxification enzymes to be induced by xenobiotic and the relationship between elevated detoxifying enzyme levels and tolerance to chemical insecticides. 53 Our work demonstrates that Cadmium chloride and Lead nitrate exposure against larval tolerance and antioxidant enzymes. Our results confirm that both Cd and Pb heavy metals induced toxicity and significantly increased antioxidant enzymes.…”
mentioning
confidence: 99%
“…The formation of ROS in atmospheric SOA and the genotoxic effect of oxidative stress caused by PM exposure have been documented by a number of studies (e.g. Risom et al, 2005;Valavanidis et al, 2008;Rattanavaraha et al, 2011;Oh et al, 2011;Fu et al, 2012).…”
Section: Cluster Analysismentioning
confidence: 99%
“…However, SOA modelling studies indicate that they can account for a significant fraction of SOA mass formed by substituted benzene oxidation (Ruggeri et al, 2016), which translates into ambient concentrations of several ng m −3 in very polluted environments (such as in Yuan et al, 2013; Table S10). The formation of endoperoxides and epoxides and of other reactive oxygenated organic compounds, such as those in Clusters 7 and 8, was hypothesized by Fu et al (2012) to explain the DNA damage caused by photodegraded aromatic compounds. Moreover, the finding of biogenic SOA components with potential mutagenic properties (Cluster 0 and some compounds in Clusters 7 and 8) is in agreement with the results of Alves et al (2016), showing that the mutagenicity of the aerosol is enhanced when pollution is mixed with emissions in rural areas.…”
Section: Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…60,61 This is not limited to the aged population; younger individuals exposed to various harsh environmental conditions such as infrared and ultraviolet rays, chemical pollution, and other physical stresses can also be affected. 62,63 Currently, various synthetic and natural antiaging creams using nanosize technology are available on the market with enhanced skin protection to moisturize, lift, and whiten skin. [64][65][66][67][68] Recently, Lohani et al 4 reviewed some nanoproducts produced by few companies for enhanced beauty, such as Hydra Zen Cream, Revitalift, and Skin Caviar Ampoules that contain phytocompounds, using various nanotechnologies.…”
Section: Phytoconstituent-based Nanocosmeceuticals For Skin Therapy Nmentioning
confidence: 99%